American Girl and the Brand Gestalt: Closing the Loop on Sociocultural Branding Research - Diamond, Nina; Sherry, John F.; Muñiz, Albert M.; McGrath, Mary Ann; Kozinets, Robert V.; Borghini, Stefania (Journal of Marketing, 2009)
This article describes an investigation of the American Girl brand that provides a more complete and holistic understanding of sociocultural branding. Recent research on emotional branding, together with prior work on brands’ symbolic nature and their role as relationship partners, represents a significant shift in the way marketers think about brands and brand management. However, a full understanding of powerful and emotionally resonant brands has been elusive, in part because sociocultural branding knowledge has accumulated in a piecemeal way and lacks coherence and integrity. In addition, powerful brands are extraordinarily complex and multifaceted, but in general they have been studied from a single perspective in a single setting. On the basis of a qualitative exploration of the American Girl brand that is both deep and broad, the authors posit that an emotionally powerful brand is best understood as the product of a complex system, or gestalt, whose component parts are in continuous interplay and together constitute a whole greater than their sum. Studying American Girl from the perspectives of various stakeholder groups in many of the venues in which the brand is manifest, the authors attempt to close the sociocultural branding research loop and identify implications for brand management.